Stability Analysis of Ginger (Zingiber officinale) Emulsion Affected by Iota Carrageenan. (September 2019) - Al-Baarri, A N; Legowo, A M; Pramono, Y B; Rizqiati, H; Pratama, Y; Masykuri,; Abduh, S B M; Nurwantoro,; Septyaningrum, A; Saraswati, R O; Puspitoasih, A D; Lestari, F P; et al.
Abstract: Ginger is commonly used by Indonesian community as a main ingredient for making traditional beverages. Separation of solutions in the production process of traditional beverage based on ginger emulsions is often found and may reduce consumer interest. Addition of iota carrageenan is expected to increase emulsion stability that could be detected by the amount of sedimentation. This study was aimed to determine the emulsion stability of ginger emulsion with the addition of iota carrageenan. Ginger emulsion formulation contained iota carrageenan was prepared from 1–3% b/v of iota carrageenan added to 10–30% v/v ginger emulsion. The heat was applied to emulsion at 70°C. Emulsion stability was analysed by spectral analysis using UV- Vis spectrophotometer and calculating the amount of separated sediment for 10 minutes. The percentage analysis was applied to measure the emulsion stability. The results showed that iota carrageenan was suitable to maintain the emulsion stability up to the 10 minutes with while no iota addition was less maintain the stability. It showed that iota carrageenan could enhance the ginger emulsion.